Karakteristik Penulisan Berita dalam Kolom Berita Bantul di Web. Bantulkab.go.id - Putri, Tiva Merlinda; Wijayanti, Dedi (Jurnal Riset Daerah, 2021)
Research on news characteristics is needed because guarding an online media is not an easy matter. Each media must have its own character that differentiates it from other media, as well as online media. Ordinary readers find the character of the media through the presentation of the news. Even though the news or information published is the same, the media must have their own point of view that makes their identity. Starting from these different characteristics, research on the characteristics of online news published by the Bantul Regional Government on the bantulkab.go.id web is interesting to be explored more deeply. The data collection technique used in this study was to use the reading note technique. The subject of this research is in the form of news texts contained in the website bantulkab.go.id June-August 2020 edition. Data reduction was carried out in two stages. First, carefully read the news on the website bantulkab.go.id, June-August 2020 edition. Furthermore, note the use of news actuality categories and types of news terraces found in the June-August 2020 edition of the bantulkab.go.id web into the card. data. Based on the research results, the category of news actuality contained in the website bantulkab.go.id June-August 2020 edition includes categories of calendar actuality, time actuality, and issue actuality. The number of data included in the calendar actuality is 4 data, the actual time is 3 data, and the problem actuality is 13 data. Meanwhile, the types of news terraces contained in the web bantulkab.go.id edition of June-August 2020 include 5 data on who lead (which news terrace), 4 as many as 2 data, what lead (what news terrace), 2 data, when lead (when the news core) as much as 2 data, where the lead (where the news is) as much as 3 data, why lead (why news terrace) as much as 4 data, and how lead (how the news is) as much as 2 data.